Mortgage loan Credit Collectibility as an Early Warning System in Credit Risk Mitigation (Study at Bank Mandiri in 2026) - Denis Anisa; Listri Herlina; Astrin Kusumawardani (International Journal of Business, Management and Economics, 2026)
This study aims to measure credit risk in Home Ownership Loan (MORTGAGE LOAN) financing at Bank Mandiri using collectibility indicators as an Early Warning System (EWS) against potential Non-Performing Loans (NPL). Using a descriptive quantitative approach, the study analyzed secondary data comprising 306 accounts in Collectibility 2A (Special Mention) as of May 13, 2026, with a total outstanding balance of Rp 142.44 billion. Results show that 53% of debtors currently in Kol 2A were previously in current status (Kol 1), indicating a new wave of credit quality deterioration undetectable by NPL ratios alone. A total of 30 accounts (9.8%) are in the critical segment with arrears exceeding Rp 10 million. These findings confirm that mid-tier collectibility movements can serve as effective early warning signals, enabling banks to adopt preventive rather than reactive risk management approaches.